Empowering Al Asror Students Through Agropreneurship to Improve Food Security - Widiyanto; Sulhadi; Raharjo, Teguh Hardi; Swastika, Najwa Abel; Utami, Lastri (Universitas Negeri Semarang, 2025)
This community service article discusses efforts to empower students at the Al Asror Islamic Boarding School in Semarang City through the agropreneurship program as a strategy to improve food security. The background of this activity is based on the importance of equipping students with practical skills that are relevant to local potential, while contributing to strengthening food independence in the Islamic boarding school environment and the surrounding community. The purpose of this program is to foster an entrepreneurial spirit in agriculture among students, provide knowledge and technical skills in plant cultivation, and create a sustainable Islamic boarding school-based food security model. The implementation method includes a series of activities such as training, mentoring, direct practice, and facilitation of access to resources and markets. The expected results of this program include increasing the knowledge and skills of students in agropreneurship, the emergence of agricultural business units managed by students, and increasing the availability and access to safe and nutritious food in the Islamic boarding school environment. This empowerment program is expected to be a model for other Islamic boarding schools in developing agropreneurship potential to support national food security.